2021
DOI: 10.3390/molecules26154609
|View full text |Cite
|
Sign up to set email alerts
|

Single Origin Coffee Aroma: From Optimized Flavor Protocols and Coffee Customization to Instrumental Volatile Characterization and Chemometrics

Abstract: In this study, the aroma profile of 10 single origin Arabica coffees originating from eight different growing locations, from Central America to Indonesia, was analyzed using Headspace SPME-GC-MS as the analytical method. Their roasting was performed under temperature–time conditions, customized for each sample to reach specific sensory brew characteristics in an attempt to underline the customization of roast profiles and implementation of separate roastings followed by subsequent blending as a means to tailo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…These studies considered that different roasting degrees (light, medium, dark) contributed to diverse classes of VOCs including, remarkably, the compounds 2-ethylpyrazine, 3-ethyl-2,5-dimethylpyrazine, 4-vinylguaiacol, 2,3-pentanedione, 2-methylbutanal, 2-ethylguaiacol, 2,5-dimethylpyrazine and 2,3-dimethylpyrazine. 71,72 It has been indicated that light roasting, widely utilized in a cup test for sensory evaluation of green seed quality, produces volatile compounds such as furfural (sweet almond notes) and 2-methyl-butanol (buttery notes), which have a strong influence on aroma. With an increase in the degree of roasting (from light to medium), some compounds such as furans and volatile acids that are responsible for floral and fresh flavor become less crucial, probably resulting from losses as temperature increases, or from exposure to a higher temperature for a long time.…”
Section: Roastingmentioning
confidence: 99%
“…These studies considered that different roasting degrees (light, medium, dark) contributed to diverse classes of VOCs including, remarkably, the compounds 2-ethylpyrazine, 3-ethyl-2,5-dimethylpyrazine, 4-vinylguaiacol, 2,3-pentanedione, 2-methylbutanal, 2-ethylguaiacol, 2,5-dimethylpyrazine and 2,3-dimethylpyrazine. 71,72 It has been indicated that light roasting, widely utilized in a cup test for sensory evaluation of green seed quality, produces volatile compounds such as furfural (sweet almond notes) and 2-methyl-butanol (buttery notes), which have a strong influence on aroma. With an increase in the degree of roasting (from light to medium), some compounds such as furans and volatile acids that are responsible for floral and fresh flavor become less crucial, probably resulting from losses as temperature increases, or from exposure to a higher temperature for a long time.…”
Section: Roastingmentioning
confidence: 99%
“…24 Meanwhile, the VOCs in green coffee were changed after roasting, which were also the reason for the difference. 6 The results of significance analysis showed that the contents of acids and esters in fresh green coffee (in 2020) changed significantly from 2019 to 2015, alcohols, aldehydes and alkenes changed significantly from 2018 to 2015, and ketones changed significantly from 2016 to 2015.…”
Section: Resultsmentioning
confidence: 98%
“…As observed in Figure 4 D, the content of 2-furanmethanol did not have significant changes between fermentation the processes and times, due to the mechanisms of reaction necessary for the synthesis of 2-furanmethanol, such as the Maillard reaction, and other thermal processes, such as oxide thermal degradation of polyunsaturated fatty acids, thiamine, nucleosides, sugars presented during caramelization, carbohydrates, ascorbic acid, and unsaturated fatty acids degradation, processes that require thermal intervention [ 44 ]. Moreover, 2-furanmethanol adds roasted aromas, and it is generated by the thermal process that degrades carbohydrates and sugars, such as hexoses and pentoses [ 45 ]; but the content of 2-furanmethanol cannot be high, because it generates an undesirable burnt and bitter smell [ 44 ].…”
Section: Resultsmentioning
confidence: 99%